Environmental Services on the Public Green Open Space using Dpsir Approach: Study Case at Mataram City - Agum Muladi; Joni Safaat Adiansyah; Harry Irawan Johari (School of Postgraduate Studies, Diponegoro Univer, 2024)
The existence of public green open spaces provides a number of benefits for the community and the surrounding environment. This study aims to assess the environmental service function of public green spaces in Mataram City using several environmental analysis approaches. The research method used a quantitative descriptive approach with the research sample being Pagutan green space and Udayana green space. The research time was conducted from June to July 2023 with research instruments namely interviews, and observations. Some of the methods used are spatial analysis, ecosystem service analysis, and DPSIR analysis. Based on the DPSIR approach, the service function in public green spaces is triggered (Drivers) by the existence of several regulations that require urban areas to have 30% of their area used as green spaces. Pressures faced by public green spaces include an increase in the number of vehicles and population every year. Existing conditions (States) show differences in the value of the measurement of noise, temperature and air quality parameters in RTH Udayana and RTH Pagutan. The impact felt by the presence of RTH shows that some environmental parameters for noise range from 12.42-20.08 dB, temperature ranges from 0.83-1.07oC and air quality (TSP, PM10, SO2, CO, O3, Humidity) show a difference between RTH and non-RTH. Response to (drivers), (pressure), (states), and (impact) variables that have been formulated using SWOT analysis is to coordinate and cooperate all parties both government, private, and community related to planning, structuring and utilization of public green spaces, as well as regular monitoring to ensure the sustainability of environmental services produced by public green spaces.